STUDY OF AGGLOMERATION FINE COAL USING MEDIUM OF USED FRYING OIL BIODIESEL - SAEPUDIN , DIDIN
The use of coal as energy source nowadays is very significant to meet both domestic and foreign demands. In regard with this, government has determined coal as an alternative energy source to bring Energy Mix 2025 into reality. To respond the more and more demands of coal, the product volume is increased. This increase not only result in the desired product amount, but also waste in a form of particles of fine coal threatening the ecosystem. Making use of these will not only keep the environment balanced but also give economical value. The process of fine coal agglomeration with biodiesel is expected to reduce the problem above. The biodiesel used is used frying oil in which the character is similar to the diesel oil, renewable, pollution free, does not contain sulphur and environmentally friendly. The experiment of agglomeration process is conducted in laboratory scale by using container and mechanic impeller made of stainless steel with sub-bituminus coal from Berau, East-Kalimantan. In this study, the influence of stirring velocity, stirring length, coal fraction size as well as additive are investigated to find out the profile of each variable toward the agglomeration results (%-organic matter recovery and %-ash rejection). The agglomeration experiment conducted without additive shows that the best condition of operation is at the 1200 rpm impeller velocity with 3 minutes by using pure biodiesel (B100). The use of 40% oil with solid matter percentage of 1,5% and the fraction size of -75 ?m can increase %-organic matter recovery to reach 99,90%. Meanwhile, the use of oil with concentration of 30% at the fraction with size of 150+75 ?m can give significant influence to gain %-ash rejection which is 61,68%. Furthermore, at operation condition and parameter of the same variable, of the decreasing of ashes content level is still possible to increase by using additive substance of CMC (carboxyl metil cellulose) with the increase attainment of 83,97%.